KARAKTERISTIK ENKAPSULAT EKSTRAK ASETON DAUN SINGKONG (Manihot esculenta C.) PADA PERLAKUAN JENIS DAN KONSENTRASI ENKAPSULAN - Ginting, Kesia Teodora Br; Wartini, Ni Made; Wrasiati, Luh Puu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): Juni, 2022)
Cassava leaf extract can be developed as a natural food coloring. Food coloring from cassava leaf acetone extract is made in powder form to make it easier to use and more stable in storage. This study aims to determine the effect of the type and concentration of encapsulation on the characteristics of the acetone extract of cassava leaf natural dye and determine the best type and concentration of encapsulant to obtain cassava leaf natural dye acetone extract encapsulate. This study used a factorial randomized block design with two factors. The first factor is the type encapsulant (maltodextrin and gum arabic) and the second factor is the concentration (5%, 10%, and 15%). The objective data obtained was then tested by analysis of variance and if there was an effect of treatment on the observed variables, the analysis was continued with the Tukey test. The results showed that treatment interactions had an effect on, yellowness level (b*), total chlorophyll and encapsulation efficiency but had no effect on yield, water content, redness level (a*), brightness level (L*). Treatment of gum arabic type with a concentration of 10% is the best treatment to produce acetone extract encapsulate natural dye of cassava leaves with yield characteristics of 95,55%, water content 10,69%, solubility 89,50%, the total chlorophyll was 3.42%, brightness level (L*) of 21,21, the level of redness (a*) was 6.30, the level of yellowness (b*) was 13.18, and the encapsulation efficiency was 89.73%.